REPORTED CASES OF HIV IN NOVA XAVANTINA – MATO GROSSO – BRAZIL - Barbosa, Kassandra Aparecida Faustino; de Sousa, Ricardo Firmino (Seven Editora, 2026)
The study analyzed the relationship between HIV and the LGBTQIA+ population, focusing on challenges and advances in prevention, as well as the epidemiological reality of Nova Xavantina–MT. The research had a quantitative approach and used data from the Notifiable Diseases Information System (SINAN) covering the period from 2009 to 2025, complemented by interviews with professionals from the Specialized Care Service and Testing and Counseling Center (SAE/CTA). The results showed a higher incidence of cases among men, especially young adults, and a predominance of notifications among heterosexual and mixed-race individuals. It was also observed that factors such as stigma, discrimination, informational inequality, and barriers to accessing health services directly influence testing, early diagnosis, and adherence to treatment. The implementation of SAE/CTA in the municipality resulted in expanded testing, provision of PrEP and PEP, distribution of supplies, and strengthening of educational actions. Despite the advances, structural challenges persist, including funding limitations, inequality in access to specialized services, and ongoing discrimination against LGBTQIA+ individuals and people living with HIV. It is concluded that combined prevention, strengthening public policies, and promoting welcoming strategies are essential to reduce virus transmission and improve the quality of life of vulnerable populations.